Improvement of Science Learning Result on Classification of Living Things through E-LKPD PjBL for Class VII Students - Sari, Susi Novita; Wulandari, Tabitha Sri Hartati (Universitas Negeri Semarang, 2025)
This study aims to test the application of PjBL-based E-LKPD can be an effective strategy in improving students' understanding of the concept of classification of living things and improving student learning result. This research is a classroom action research with a Quantitative approach. This design involves two cycles, each of which consists of four stages, namely planning, action implementation, observation, and reflection. The subjects of this study were students of class VII - G with a total of 30 students. The instruments used in this study were the developed E-LKPD PjBL, student activity observation sheets, and learning result tests. Based on the results of data analysis of student scores in Cycle 1, it was noted that 60% of students were categorized as complete, 40% of students were not complete. Cycle 2 results showed a significant increase in the percentage of student learning completeness, which reached 86.67% and 13.33% of students were not yet complete. Based on this, it can be concluded that E-LKPD PjBL can increase the value of science learning result on the material Classification of Living Things.